Delineation of Turmeric Zones in Tamil Nadu - N Sankaran, T N Balasubramanian, K Kandiannan, K K Chandaragiri (Journal of Spices and Aromatic Crops, 2001)
Tamil Nadu is having 30 districts, spread over 13 million ha. in 7 agro-climatic zones and lies between 8°5' and 13°5' north latitude and 76°15' and 80°20' eastern longitude. The average annual rainfall is 1010 mm with 54 rainy days. Tamil Nadu ranks third place in area under turmeric (11 %) next to Andhra Pradesh (39 %) and Orissa (18%) and second place in production (19%) next to Andhra Pradesh (49%).